2015
DOI: 10.1177/1756283x14564674
|View full text |Cite
|
Sign up to set email alerts
|

Triple modality testing by endoscopic retrograde cholangiopancreatography for the diagnosis of cholangiocarcinoma

Abstract: A triple modality approach results in a marked increase in sensitivity for the diagnosis of cholangiocarcinoma compared with single modality testing such as brush cytology and should be considered in the evaluation of indeterminate or suspicious biliary strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 48 publications
3
71
0
1
Order By: Relevance
“…79,80 Overall, the sensitivity of brush cytology as a single modality of diagnosis is around 55% based on published data. 81,82 Similar findings were reported in the meta-analysis of brush cytology. In the study with 747 patients with PSC-related strictures, it demonstrated sensitivity and specificity of 43% and 97%, respectively.…”
Section: Ercp Ptc Biopsy and Brush Cytologysupporting
confidence: 77%
“…79,80 Overall, the sensitivity of brush cytology as a single modality of diagnosis is around 55% based on published data. 81,82 Similar findings were reported in the meta-analysis of brush cytology. In the study with 747 patients with PSC-related strictures, it demonstrated sensitivity and specificity of 43% and 97%, respectively.…”
Section: Ercp Ptc Biopsy and Brush Cytologysupporting
confidence: 77%
“…Since the sampling area for ductal biopsies is limited, complementary biliary brushings should be considered in all patients. The sensitivity and specificity for the detection of CCA by ductal biopsy in published studies varies from 30-88%, and 97-100%, respectively (106). Combining brush cytology and biopsy has a sensitivity varying from 47-86% and specificity of 97-100%.…”
Section: Ductal Biopsymentioning
confidence: 99%
“…Combining brush cytology and biopsy has a sensitivity varying from 47-86% and specificity of 97-100%. A study (106) assessing the accuracy of triple modality: brush cytology, biopsy and FISH or their combination demonstrated that brush cytology alone had a sensitivity of 42%, specificity of 100%, positive predictive value of 100% and negative predictive value of 88%. Triple sample assessment modality markedly improved the overall sensitivity (82%), specificity (100%), positive predictive value (100%), and negative predictive value (87%).…”
Section: Ductal Biopsymentioning
confidence: 99%
“…[9][10][11][12] Studies have also evaluated fluorescence in situ hybridization (FISH) using probes for genetic alterations associated with CCA, with reported sensitivities ranging from 38% to 58% and specificities between 91% and 100%. 13,14 Newer FISH probes may increase the sensitivity to 65% and next generation genetic sequencing techniques are also promising, but the data is still limited. 15 The sensitivity may increase up to 59% when combining FISH with cytology and up to 82% when combined with both brushing and biopsy.…”
Section: Sampling Of Biliary Pathologymentioning
confidence: 99%